Estimating the non-linear effects of urban built environment at residence and workplace on carbon dioxide emissions from commuting - Liu, Qingchun; Zhao, Peixiong; Zhang, Yingying; Zhang, Zhihui; Yang, Jun (Frontiers in Public Health, 2022)
Understanding the relationship between CO2 emissions from commuting (CEC) and the built environment is crucial for sustainable transportation and land-use policymaking during the process of constructing a low carbon city. Previous studies usually assume that the relationship is linear, which may lead to inaccurate CEC prediction and ineffective policy. Using daily travel survey data of residents in the central city of Jinan, this study adopted a gradient boosting decision tree model to explore the threshold effect and the nonlinear relationship between built environments and CEC. Our ﬁndings suggest that 40% of CEC is related to the workplace environment, which is higher than the residential environment and other socioeconomic variables. The five most important variables are road density within 1 km radius of the workplace (13.493%), distance to the center at workplace and residence (10.908%, 10.530%), population density at workplace (9.097%) and distance to bus stop from the residence (8.399%). Distance to city center plays the most important role and its nonlinear relationship reflects the influence of the urban spatial structure of Jinan on CEC. Furthermore, the thresholds and nonlinear relationships provide planning guidelines to support urban planning development policies for low carbon city.